WAYS OF STABILIZING THE QUALITY INDICATORS OF CORN GRAIN DURING LONG-TERM STORAGE - Завадська, Оксана; Бондарєва, Леся; Домоцький, Микола (Modern engineering and innovative technologies, 2023)
The article presents the results of a study of changes in moisture content, starch and protein of corn grains of three hybrids grown in the conditions of Polissia of Ukraine during 9 months of storage. It was established that the intensity of changes in